Interaction of natural killer cells with neutrophils exerts a significant antitumor immunity in hematopoietic stem cell transplantation recipients. (21st November 2015) - Ueda, Ryosuke; Narumi, Kenta; Hashimoto, Hisayoshi; Miyakawa, Reina; Okusaka, Takuji; Aoki, Kazunori
Abstract : Natural killer (NK) cells undergo homeostatic proliferation (HP) early after syngeneic hematopoietic stem cell transplantation. NK cells undergoing HP are highly activated, leading to antitumor effect. Neutrophils support survival of mature NK cells in tumor. Abstract: Autologous hematopoietic stem cell transplantation (HSCT) can induce a strong antitumor immunity by homeostatic proliferation (HP) of T cells and suppression of regulatory T cells following preconditioning‐induced lymphopenia. However, the role of innate immunity including natural killer (NK) cells is still not understood. Here, first, we examined whether NK cells exert an antitumor effect after syngeneic HSCT in a murine colon cancer model. Flow cytometry showed that NK cells as well as T cells rapidly proliferated after HSCT, and the frequency of mature NK cells was increased in tumor during HP. Furthermore, NK cells undergoing HP were highly activated, which contributed to substantial tumor suppression. Then, we found that a large number of neutrophils accumulated in tumor early after syngeneic HSCT. It was recently reported that neutrophil‐derived mediators modulate NK cell effector functions, and so we examined whether the neutrophils infiltrated in tumor are associated with NK cell‐mediated antitumor effect. The depletion of neutrophils significantly impaired an activation of NK cells in tumor and increased the fraction of proliferative NK cells accompanied by a decrease in NK cell survival. The results suggested that neutrophils in tumor prevent NK cells from activation‐induced cell death during HP, thus leading to a significant antitumor effect by NK cells. This study revealed a novel aspect of antitumor immunity induced by HSCT and may contribute to the development of an effective therapeutic strategy for cancer using HSCT.